Lifecourse predictors of adult respiratory function: results from the Newcastle Thousand Families Study. Issue 9 (11th April 2008) - Tennant, P W G; Gibson, G John; Pearce, M S
Abstract : Background: Impaired development in utero is suggested to increase the risk of poor respiratory health in adulthood, although a consensus has not been reached. A possible explanation for discrepancies between previous studies is inconsistent controlling for potential confounding factors, particularly childhood infections. Also, little is known regarding the relative importance of factors operating at different stages of the lifecourse. We have used detailed longitudinal data from the Newcastle Thousand Families cohort to assess the impact of birth weight, and various other factors acting throughout the lifecourse, on predicting forced expiratory volume in 1 s (FEV1 ). Methods: Detailed information was collected prospectively during childhood, including birth weight, childhood infections and socioeconomic circumstances. At age 49–51 years, 412 study members attended for clinical examination and measurement of FEV1 . These data were analysed in relation to a range of factors from across the lifecourse using linear regression models. Results: After adjustment for all other significant variables, increasing birth weight, standardised for sex and gestational age (p = 0.011), being breast fed for more than 4 weeks (p = 0.017), less frequent childhood lower respiratory tract infections (LRTI) (p = 0.015), non- smoking (p<0.001), lower body fat percentage (p = 0.010), male sex (p<0.001), no history of asthma (p = 0.013) and greater adult height (p<0.001) were all independently associated with higher adult FEV1 . Conclusion: Adult lung function is influenced by numerous factors during an individual's lifetime, acting both directly and indirectly throughout the lifecourse. As expected, sex, height and smoking were the most important predictors of FEV1, but birth weight, breast feeding and childhood LRTIs also contributed significantly.